Changes in bird‐migration patterns associated with human‐induced mortality. Issue 1 (27th August 2016) - Palacín, Carlos; Alonso, Juan C.; Martín, Carlos A.; Alonso, Javier A.
Abstract: Many bird populations have recently changed their migratory behavior in response to alterations of the environment. We collected data over 16 years on male Great Bustards (Otis tarda), a species showing a partial migratory pattern (sedentary and migratory birds coexisting in the same breeding groups). We conducted population counts and radio tracked 180 individuals to examine differences in survival rates between migratory and sedentary individuals and evaluate possible effects of these differences on the migratory pattern of the population. Overall, 65% of individuals migrated and 35% did not. The average distance between breeding and postbreeding areas of migrant individuals was 89.9 km, and the longest average movement of sedentary males was 3.8 km. Breeding group and migration distance had no effect on survival. However, mortality of migrants was 2.4 to 3.5 times higher than mortality of sedentary birds. For marked males, collision with power lines was the main cause of death from unnatural causes (37.6% of all deaths), and migratory birds died in collisions with power lines more frequently than sedentary birds (21.3% vs 6.3%). The percentage of sedentary individuals increased from 17% in 1997 to 45% in 2012. These results were consistent with data collected from radio‐tracked individuals: The proportion of migratory individuals decreased from 86% in 1997–1999 to 44% in 2006–2010. The observed decrease in the migratory tendency was not related to climatic changes (temperatures did not change over the study period) or improvements in habitat quality (dry cereal farmland area decreased in the main study area). Our findings suggest that human‐induced mortality during migration may be an important factor shaping the migration patterns of species inhabiting humanized landscapes.